Effect of Micronutrients on Yield and Quality of Guava cv Lucknow 49 in Sodic Soil - Janaki, D; Kumar, S; Rajammal, T Sherene Jenita (Journal of Soil Salinity and Water Quality, 2023)
Tamil Nadu occupies 4.7 lakh ha of salt-affected soils, in which 3.0 lakh ha area is under inland and 1.7 lakh ha is coastal. Among the 3.0 lakh inland salt affected soils, 2.0 lakh ha have developed alkalinity and 1.0 lakh ha salinity. In Trichirappalli, the study area a total 18,155 ha area falls under alkalinity problem. Guava is one of the commercial fruit crops comes well under salt-affected soils. The main problem in yield reduction in guava is due to micronutrient deficiency. Hence, the present investigation was conducted at Horticultural College and Research Institute for Women, Tiruchirappalli during 2020-2021 in clay loam texture with pH 9.23, ESP-36.52%. The experiment was laid out in Randomized Block Design (RBD) on guava cv. Lucknow -49 planted at 3m × 2m spacing with seven treatments replicated three and ten number of plants per replication were taken. The treatments comprised of T1 – Control, T2 – RDF alone ( 300:150:150 g NPK/tree), T3 – RDF + 100% MN Mixture TN Govt. rec.@500g/tree,T4 – RDF + 125% MN Mixture TN Govt. rec.@500g/tree ,T5 – RDF + 100% Enriched FYM TN Govt. rec.@500g/tree,T6 - RDF + 125% Enriched FYM TN Govt. rec.@500g/tree,T7- RDF +1% foliar spray of 100% MN Mixture TN Govt (II approximation) rec .The foliar application of these treatments was made at three times of new flush, 30 and 70 days after flowering. The results revealed that the application of RDF + 100% Enriched FYM TN Govt. rec.@500g/tree recorded highest 50% flowering (33.6%), fruit retention (51.5%), highest yield (42.3 Mg ha-1) and quality parameters like TSS (12.80brix) and lowest acidity (0.42%) followed by treatment RDF + 125% MN Mixture TN Govt. rec.@500g/tree and the same treatment recorded the BC ratio of 3.64 while the control with BC ratio of 2.75.